THE ANALYSIS OF SATURATED HYDRAULIC CONDUCTIVITY ON YELLOW BAMBOO (Bambusa vulgaris schard Es.J.C) STICK - Jenni Aulia Perucha (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This research aims to determine the value of saturated hydraulic conductivity (Ks) yellow bamboo in varioustreatments as a tool for subsurface irrigation purposes. This research has been conducted on March until April2015. This research was conducted in the Laboratory of Power and Agricultural Machinery, AgriculturalEngineering Department, Faculty of Agriculture, University of Lampung. The Ks of yellow bamboo researchconducted on6 treatments , those are the epidermis andendodermis thatnot scraped( C1 ); layers of the epidermisand endodermis scraped until 0,5 cmthickness ( C2 ); layers of the epidermis and endodermis scraped up as thickas 0,7 cm ( C3 ); layers of the epidermis and endodermis scraped up as thick as 0,9 cm ( C4 ); layers of theepidermis and endodermis scraped up as thick as 1,1 cm ( C5 ); layers of the epidermis and endodermis scrapedup as thick as 1,3 cm(C6 ), thenall treatments is performed in three repetitions and endurance for5weeks.Basedonthe research that has beendone , theKs of yellowbamboowith C1 treatment is 0 cm/sec, C2was 7,24 x 10-8 cm/sec; C3 was 6,87 x 10-8 cm/sec; C4was 8,56 x 10-8 cm/sec; C5was 6,93 x 10-8 cm/sec; and C6was 7,06 x 10-8 cm/sec. It canbe showthat the higher bamboo’swater absorbing ability the higher hydrolic conductivity’s value thatobtained. Whereas, the lower bamboo’s water absorbing ability the lower hydrolic conductivity’s value thatobtained.Keywords : hydraulic conductivity , endurance , yellowbamboo